Pengaruh Penduduk, PDRB Perkapita dan Hotel Terhadap Penerimaan Pajak Daerah Kabupaten/Kota di Sumatera barat - Tomo Pramana Putra; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study aims to analyze the effect of population, GDP per capita and hotels on local tax revenues in districts / cities in West Sumatra. The data used are secondary data in the form of panel regression in 19 districts / cities in West Sumatra province. The source of this data is the West Sumatra Central Statistics Agency (BPS). The variables used in this study are population (X1), GDP per capita (X2) and hotels (X3). The methods used in this research are: (1) Panel Regression Model (2) Classical Assumption Test (3) t test (4) f test. The results of this study indicate that (1) total population has a negative and significant effect on local tax revenues in regencies / cities in West Sumatra. (2) PDRB Per capita has a positive and significant effect on local tax revenues in districts / cities in West Sumatra. (3) The number of hotels has a positive and significant effect on local tax revenues in districts / cities in West Sumatra.